Monitoring the prevalence and antibiotic resistance of Acinetobacter baumannii in a multidisciplinary hospital in Astana - Sutimbekova, Н.С.; Bisenova, Н.М.; Dusmagambetov, М.У.; Urekeshov, Б.С.; Ergalieva, А.С.; Bekniyazova, Г.А. (BULLETIN of the L.N. Gumilyov Eurasian National University. BIOSCIENCE Series, 2025)
Acinetobacter baumannii is one of the most dangerous hospital-acquired infections, leading to death in patients with weakened immune systems, especially in intensive care units. Many strains resist carbapenems, the "antibiotics of last resort," making treatment extremely difficult. In this regard, the frequency of isolation and the level of resistance of A. baumannii strains in patients of the pediatric cardiac surgery department (PCSD) and the department of anesthesiology, resuscitation, and intensive care (DARIC) for the period 2015 to 2022 were studied. A retrospective analysis of the results of bacteriological culture of various biomaterials for the isolation of pathogenic flora taken from adult patients hospitalized in DARIC and PCSD patients over 8 years, with determination of antibiotic sensitivity was carried out. A total of 8696 clinical isolates were recovered, of which A. baumanniiaccounted for 629 cases, primarily from DARIC (203) and PCSD (426). Identification was carried out on a microbiological analyzer "Vitek 2 - Compact" (bioMerieux, Marcy I'Etoile, France). Antimicrobial activity was studied by the method of minimum inhibitory concentrations ("Vitek 2 - Compact"). Isolate distribution analysis shows a significant difference in the detection rate of A. baumannii in DARIC and PCSD: 13.5% in DARIC versus 5.8% in PCSD. Antibiotic resistance analysis revealed an increase in resistance to all antibiotics used, particularly in DARIC, where resistance to levofloxacin was 93.3%, meropenem 92.8%, gentamicin 90.6%, ciprofloxacin 89.7%, and imipenem 86.1%. PCSD also recorded an increase in resistance, but within 27%. Thus, the comparative analysis of the frequency of isolation of A. baumannii in DARIC units was higher than in PCSD. An increase in resistance to all tested antibiotics was noted in DARIC and PCSD units, except for colistin.